2016
DOI: 10.3329/jujbs.v3i1.28277
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fixing efficiency and physiological characteristics of Azospirillum isolates from the paddy fields of North Bengal

Abstract: The microbial activity of ten selected Azospirillum isolates was measured in terms of the amount of CO 2 evolved by the isolates after incubation for 5 days which ranged from 6.88 to19.25 mg. Nitrogen fixing efficiency all of the isolates was determined by microkjeldhal method and the nitrogen fixing efficiency ranged from 10.03 to 13.11 mg N/g substrate. The growth of Azospirillum isolates was significant affected by different physiological factors such as pH, temperature and salinity. Most of the isolates sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…(Table 2). Among other factors, the nitrogen fixing abilities of Azospirillum isolates depend on nitrogenase enzyme activity (Sant'Anna et al 2011). Hossain et al (2014 reported that nitrogen fixing efficiency of Azospirillum sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Table 2). Among other factors, the nitrogen fixing abilities of Azospirillum isolates depend on nitrogenase enzyme activity (Sant'Anna et al 2011). Hossain et al (2014 reported that nitrogen fixing efficiency of Azospirillum sp.…”
Section: Resultsmentioning
confidence: 99%
“…Azospirillum colonizes the root region of crop plants in large numbers and fixes substantial amount of nitrogen (Saikia et al 2013). Crop production response to bacteria with Azospirillum inoculants was almost equivalent to that of application of 15 -20 kg N/ha (Hossain et al 2014). Inoculation with Azospirillum brasilense increased grain production of maize (Morais et al 2016).…”
Section: Introductionmentioning
confidence: 92%
“…After completing the requisite incubation, the plates were flooded with iodine solution to test the isolates starch digestion capacity. A yellow zone around the colony indicated starch hydrolysis, while a blue/black area indicated starch presence (Hossain et al, 2015).…”
Section: Starch Hydrolysis Testmentioning
confidence: 99%
“…The highest efficiencies of nitrogen fixation first reported by Dobereiner and Day, (1976) 115 mg N 2 fixed/ g lactate which has not been reported in other studies, Okon et al, (1977) reported values of 20 to 24 mg N 2 fixed/ g substrate, while Lakshmi et al, (1977) recorded from 12 to 36 mg N 2 fixed/ g substrate, Nelson and Knowles, (1978) reached to 28 mg N 2 fixed/ g substrate, as well as Khan et al, (2001) recorded that the N 2 -fixing potentials of Azospirillum isolated from wheat fields of Dhaka ranged from 15.12 : 22.16 mg N 2 fixed/g substrate, and Azospirillum isolated from Bangladesh was fixed nitrogen and ranged from 10.08 : 28.00 mg N 2 fixed/g substrate, Kanimozhi and Panneerselvam, (2010) ranged from 3.3 to 15.6 mg N 2 fixed/g substrate, while Hossain et al, (2014) ranging from 10.03 to 13.11 mg N 2 fixed/ g substrate (malate), finally Bharathiraja, (2019) ranged from 1.03: 42.30 mg N 2 fixed/g cell weight.…”
Section: Determination Of N 2 Fixationmentioning
confidence: 99%